Nov pristop Vrhovnega sodišča RS k nepoštenosti splošnih pogojev poslovanja v potrošniških kreditnih pogodbah - Možina, Damjan (Podjetje in delo, 2024)
The paper critically analyses the new case law of the Supreme Court of Slovenia regarding the fairness assessment of contract terms in credit contracts. A foreign currency clause is considered unfair merely due to lack of transparency; as it belongs to the main subject of the contract, this causes the nullity of the entire credit contract. The Supreme Court claims that a change of case law is based on the rulings of the CJEU in the BNP Paribas cases. However, under Directive 93/13, a clause is unfair if it causes significant imbalance in contractual rights and obligations to the detriment of the consumer contrary to good faith. An additional criterion is the transparency of the clause. Furthermore, the Supreme Court, based on the principle of minimum harmonisation, considers that, in Slovenia, a clause is unfair if it either causes significant imbalance of contractual rights and obligations or is contrary to good faith. The Supreme Court interprets the transparency requirement very strictly. A bank is under a duty to notify the consumer regarding all information about the foreign currency it should have, taking into account its professional diligence; failure to disclose any such information is deemed sufficient for the unfairness of the clause and, consequently, for the nullity of the entire contract. The Supreme Court disregards the fact that the Slovenian Consumer Credit Act explicitly regulated pre-contractual information about currency risk, and that, according to Art. 1 (2) of Directive 93/13, the fairness of contract clauses directly reflecting the content of legislation or international conventions should not be assessed.
Keywords: consumer protection; contract law; EU Law; interpretation in accordance with EU law; lojalna razlaga; minimum harmonisation; načelo minimalne harmonizacije; pogodbeno pravo; pravo EU; presoja poštenosti splošnih pogojev poslovanja; unfairness of non-individually negotiated contract clauses; varstvo potrošnikov